Main Problems of Forming the Competence of Academic Writing in Future Foreign Language Teachers (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article demonstrates a relatively new direction for the Uzbek education system - academic writing. To determine the conceptual essence of the category of "academic writing", a brief analysis of some scientific works devoted to this topic was carried out; the question was raised about the importance of introducing this discipline into the educational programs of the universities of the Republic of Uzbekistan; the most difficult areas in the formation of the competence of academic writing among undergraduate and graduate students of the program "Training of Foreign Language Teachers" were identified; factors that cause difficulties in academic writing are identified and described.